Aspects of pollution in False Bay, South Africa (with special reference to subtidal pollution) - Rundgren, Carl David (Department of Biological Sciences, 2016)
False Bay is the largest (circa 1000km²) natural, coastal embayment on the South African coastline and is located between latitudes 34°04'S and 34°23'S and longitudes 18°26'E and 18°52'E at the southern tip of Africa, near Cape Town, South Africa. The semi-enclosed nature of the bay makes it unsuitable as a 'sink' for all the contaminated urban stormwater run-off and the greatly increased pollution loads entering the bay. All pollution point sources entering False Bay were identified and described, and some of these selected for detailed study, the emphasis being on the impact of some individual discharges on the subtidal macrofauna. The similar biotic characteristics of three subtidal study sites in the region of the Steenbras Water Treatment Plant discharge indicate that the general turbidity and lower salinity characteristics of eastern False Bay are more likely to be responsible for the impoverished diversity near the outfall rather than the aluminium content of the discharge. Toxicity experiments on the bivalves Choromytilus meridionalis, Mytilus galloprovincialis and Perna perna using alum and ferric sludge indicate that there are no significant short-term sub-lethal toxic effects on the rocky shore bivalves and that decreased salinities in the immediate region of the outfall (as a result of the freshwater stream input) may have a more deleterious effect. A study of eighteen subtidal sites in False Bay indicated that overall densities of subtidal macro plastic debris were low, but that there are some 'hot spots' where densities are relatively high viz., Kalk Bay, Strandfontein, Mnandi, Monwabisi and Gordon's Bay. Colonising of debris by benthic organisms does occur, mostly on white plastic. Most of the debris consisted of plastic packaging from local land-based sources, indicating that it originates from wind-blown litter left by beachgoers. The highest density at the Sunnycove Control Site occurred in January during the peak holiday season. A longer term (three years) study of the subtidal environment in the vicinity of the Marine Oil Refiners outfall pipe indicated that the lack of subtidal macro fauna is more likely due to the harsh environmental conditions (abrasion and smothering) rather than the pollution impact of the outfall. This is confirmed by the abundant, healthy and diverse community on the nearby wreck of the Clan Stuart (1917) which indicates a stable ecosystem. The complexity of False Bay - its unique topography, bathymetry, meteorology make it difficult to attain a true climatic or average circulation. This lack of a consistent conceptual overview of the False Bay physical circulation is a short-coming that needs to be urgently addressed if the dangers of pollution inputs are to be accurately assessed. An overall management policy for False Bay should be urgently formulated and an officially constituted body with legislative power is needed if holistic management of the bay is to be achieved and such a prime recreational asset preserved for future generations. Bibliography: pages 195-225.